Trade secrets law - Luigi Alberto Franzoni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2020)
The standardisation of trade secret protection was one of the goals of the TRIPs Agreement of 1998. Nevertheless, substantial differences in this protection remain across jurisdictions. When defining the optimal scope of trade secrets law, lawmakers should be aware that strong trade secret protection is likely to promote inventiveness, but it is also likely to hinder the diffusion of knowledge and prevent competition.
Keywords: K0; L1; 330; Trade Secrets Law; Intellectual Property